2019
DOI: 10.3899/jrheum.180042
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variations in Systemic Sclerosis Disease Manifestations, Internal Organ Involvement, and Mortality

Abstract: Objective.A multiethnic systemic sclerosis (SSc) cohort study to evaluate ethnic variations in disease manifestations, internal organ involvement, and survival.Methods.Adults who fulfilled the American College of Rheumatology/European League Against Rheumatism classification criteria for SSc between 1970 and 2017 were included. Self-reported ethnicity was categorized as European-descent white, Afro-Caribbean, Hispanic, Arab, East Asian, South Asian, First Nations, or Persian. The primary outcome was the time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
6
38
3
Order By: Relevance
“…compared to our study [28]. The authors, however, did not find a difference in PH prevalence between patients of various ethnicities [28].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…compared to our study [28]. The authors, however, did not find a difference in PH prevalence between patients of various ethnicities [28].…”
Section: Discussioncontrasting
confidence: 92%
“…compared to our study [28]. The authors, however, did not find a difference in PH prevalence between patients of various ethnicities [28]. This goes in line with our finding that Asian patients treated outside Asia had a similar frequency of PH than the white centre-matched comparison group and hints towards a location-driven higher prevalence of PH in Asia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the strong female predominance reported in SSc (female to male ratio 4.7:1), men with SSc are more likely to develop ILD than women with SSc (relative risk 1.24; 95% confidence interval 1.01-1.52) [31,32]. A large multi-ethnic observational study conducted in the setting of a universal healthcare system found that in comparison to white patients of European descent, patients of Afro-Caribbean descent with SSc more frequently have ILD (31% versus 53%; p=0.007) [33].…”
Section: Risk Factors For Presence Of Ildmentioning
confidence: 99%
“…4 Specifically, East Asians had esophageal dysmotility (69.0%) less frequently compared with the white population (88.0%). 4 Esophageal manometry is the gold standard to evaluate esophageal dysmotility. The classic sclerosis esophagus is defined when SSc patients have no peristalsis in the distal esophagus and hypotensive lower esophageal sphincter (LES) pressure on manometric examination.…”
Section: Introductionmentioning
confidence: 95%